Electrolyte, preparation method thereof, electrochemical device, electrochemical energy storage device, and electric device

CN123018124APending Publication Date: 2026-10-30BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610786800.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本申请旨在提供一种电解液及其制备方法、电化学装置、电化学储能装置、用电装置,用于解决降低电芯阻抗的同时往往伴随高温,导致电池的电化学性能劣化的问题

Benefits of technology

本申请实施例中,电解液中的含硫有机化合物优先于电解液中的溶剂在正极界面发生氧化反应,可选择性在正极表面原位构筑结构致密的防护表层。该致密保护层能够有效阻隔溶剂分子与正极活性材料的直接接触,抑制高温、高倍率快充工况下电解液持续分解、电极界面腐蚀等有害副反应,减少副产物堆积与正极活性材料结构破损,从根源上缓解高温环境下电池性能快速衰减的问题,提升电芯高温储存及高温循环稳定性。同时,电解液中的含氟有机硅烷化合物具备优异的成膜特性,可在正负极界面诱导生成厚度轻薄、离子传导效率优异的正极电解质界面膜(CEI膜),能够降低电荷转移阻抗与离子穿越界面的传输阻力,为电池高倍率快充提供离子快速传导基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses an electrolyte, a preparation method thereof, an electrochemical device, an electrochemical energy storage device and an electric device. The electrolyte comprises a fluorine-containing organosilane compound and a sulfur-containing organic compound. The sulfur-containing organic compound in the electrolyte is preferentially oxidized at a positive electrode interface to in-situ construct a dense protective surface layer on the positive electrode surface. The dense protective layer fundamentally alleviates the problem of rapid performance degradation of the battery in a high-temperature environment and improves the high-temperature storage and high-temperature cycle stability of the battery. Meanwhile, the fluorine-containing organosilane compound in the electrolyte has excellent film-forming properties and can induce the generation of a positive electrolyte interface film with light thickness and excellent ion conduction efficiency at the positive and negative electrode interface, thereby reducing the charge transfer impedance and the transmission resistance of ion across the interface, and providing a basis for fast ion conduction for high-rate fast charging of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of new energy technology, specifically relating to an electrolyte and its preparation method, an electrochemical device, an electrochemical energy storage device, and an electrical device. Background Technology

[0002] Batteries, with their advantages of high operating voltage, long cycle life, low self-discharge rate, and environmental friendliness, have become one of the most promising electrochemical energy storage systems, widely used in pure electric vehicles, hybrid electric vehicles, and smart grid energy storage. With the rapid development of the new energy vehicle industry, users' demands for charging convenience are increasing, and fast charging capability has become a key technological bottleneck restricting the large-scale popularization of power batteries.

[0003] Studies have shown that the key to improving battery fast charging performance lies in reducing the impedance of the battery cell, thereby effectively suppressing the temperature rise caused by Joule heating during high-rate charging and preventing heat accumulation from adversely affecting the battery cell's lifespan and safety.

[0004] However, in related technologies, reducing cell impedance is often accompanied by high temperatures, which leads to the degradation of the battery's electrochemical performance. Summary of the Invention

[0005] This application aims to provide an electrolyte and its preparation method, an electrochemical device, an electrochemical energy storage device, and an electrical device to solve the problem that reducing cell impedance often accompanies high temperatures, leading to the degradation of battery electrochemical performance.

[0006] To solve the above-mentioned technical problems, this application is implemented as follows: In a first aspect, embodiments of this application provide an electrolyte comprising a fluorinated organosilanes compound and a sulfur-containing organic compound.

[0007] In one embodiment, the fluorinated organosilanes have the chemical formula I.

[0008] R1, R2, and R3 independently include substituted or unsubstituted groups having 1 to 5 carbon atoms, and the groups include at least one of alkyl, aryl, alkenyl, alkynyl, and alkoxy groups.

[0009] In one embodiment, the fluorinated organosilane compound includes at least one of the following chemical formulas:

[0010] In one embodiment, the sulfur-containing organic compound includes at least one of 1,3-propanesulfonate lactone, propenyl-1,3-sulfonate lactone, vinyl sulfate, vinyl sulfite, and methylene disulfonate.

[0011] In one embodiment, the mass percentage of the sulfur-containing organic compound is a%, and the mass percentage of the fluorinated organosilane compound is b%, based on the mass of the electrolyte. Wherein, the range of 'a' is 0.1 ≤ a ≤ 3.5; and / or, The range of b is 0.01≤b≤1.

[0012] In one embodiment, the range of a / b is 0.13 to 20.

[0013] In one embodiment, the electrolyte further includes oxalate phosphate, which includes at least one of lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate.

[0014] In one embodiment, the mass percentage of oxalate phosphate is in the range of 0.1% to 1% based on the mass of the electrolyte.

[0015] In one embodiment, the electrolyte further includes a first film-forming additive, which includes at least one of fluoroethylene carbonate, vinylene carbonate, difluoroethylene carbonate, fluoropropylene carbonate, and methyl vinylene carbonate.

[0016] In one embodiment, the mass percentage of the first film-forming additive ranges from 0.2% to 8% based on the mass of the electrolyte.

[0017] In one embodiment, the electrolyte further includes a non-aqueous solvent and / or a lithium salt; The non-aqueous solvent includes at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate; and / or, The lithium salt includes at least one of lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethanesulfonyl)methyl, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, and lithium hexafluorophosphate.

[0018] Secondly, this application proposes a method for preparing an electrolyte, the method being applicable to the aforementioned electrolyte, the method comprising: A second film-forming additive is obtained by mixing a fluorinated organosilane compound and a sulfur-containing organic compound. The electrolyte is obtained according to the second film-forming additive.

[0019] Thirdly, embodiments of this application provide an electrochemical device comprising a positive electrode, a negative electrode, a membrane, and the aforementioned electrolyte, wherein the membrane is disposed between the positive electrode and the negative electrode.

[0020] Fourthly, embodiments of this application propose an electrochemical energy storage device, which includes the electrochemical device described above.

[0021] Fifthly, embodiments of this application propose an electrical device including the aforementioned electrochemical energy storage device, wherein the electrochemical energy storage device serves as the power supply for the electrical device.

[0022] Compared with the prior art, this application has the following advantages: In this embodiment, sulfur-containing organic compounds in the electrolyte preferentially undergo oxidation at the positive electrode interface compared to the solvent, selectively constructing a dense protective layer in situ on the positive electrode surface. This dense protective layer effectively blocks direct contact between solvent molecules and the positive electrode active material, suppressing harmful side reactions such as continuous electrolyte decomposition and electrode interface corrosion under high-temperature, high-rate fast charging conditions. It reduces by-product accumulation and structural damage to the positive electrode active material, fundamentally alleviating the problem of rapid battery performance degradation under high-temperature environments and improving the cell's high-temperature storage and high-temperature cycling stability. Simultaneously, fluorinated organosilane compounds in the electrolyte possess excellent film-forming properties, inducing the formation of a thin, highly efficient positive electrode electrolyte interphase (CEI) film at the positive and negative electrode interfaces. This reduces charge transfer impedance and ion transport resistance across the interface, providing a foundation for rapid ion conduction during high-rate fast charging.

[0023] In summary, the electrolyte forms a synergistic system with the other two components, which effectively reduces the overall impedance of the battery cell, meets the requirements of high-rate fast charging, improves the interface stability and cycle life of the battery under high-temperature conditions, and balances the battery's fast charging performance and high-temperature service performance.

[0024] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation

[0025] The embodiments of this application will now be described in detail, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.

[0026] The applicant found that the mainstream technical approach to improving battery fast charging capabilities at present, and the industry-wide optimization strategy, involves reducing cell impedance and suppressing temperature rise during fast charging through material modification, structural optimization, and formulation adjustments. For example, in terms of negative electrode materials, surface carbon coating, doping modification (such as incorporating small amounts of amorphous carbon or carbon nanotubes), or optimization of particle morphology and size distribution of graphite or silicon-based materials can reduce the charge transfer impedance and lithium-ion diffusion impedance of the negative electrode. Furthermore, physical structure optimization methods such as thinning and pore size control of separators, full-tab structure design, and high-porosity compaction processes for electrodes are also widely used to reduce the ohmic impedance and polarization impedance of the battery cell. These technical approaches can reduce the DC internal resistance (DCR) of the battery cell to varying degrees, thereby achieving fast charging capabilities at rates from 3C to 6C.

[0027] While the aforementioned technical solutions can effectively reduce cell impedance and improve fast charging performance, they generally exhibit the common problem of high-temperature performance degradation in practical applications. For the negative electrode, the highly conductive carbon coating layer is prone to structural degradation, peeling, or interfacial film remodeling under high-temperature cycling conditions (e.g., above 45°C), leading to impedance rebound or even deterioration. Furthermore, the difference in thermal expansion between the coating layer and the current collector exacerbates interfacial failure. During long-term high-temperature float charging or cycling, the positive electrode coating layer is prone to cracking or detachment due to lattice oxygen release or lattice mismatch between the coating layer and the substrate, resulting in increased interfacial impedance. Thinning the separator and increasing its pore size weakens its dimensional stability at high temperatures, leading to excessive thermal shrinkage or pore failure, causing micro-short circuits within the cell. Therefore, existing technologies for reducing cell impedance generally sacrifice high-temperature performance, making it difficult to simultaneously meet the dual requirements of low impedance, long lifespan, and high safety in fast charging applications. Therefore, developing a technical solution that can significantly reduce cell impedance, achieve high-rate fast charging, and maintain or even improve electrochemical stability under high-temperature conditions has important industrial value and practical significance.

[0028] To address the aforementioned issues, in a first aspect, embodiments of this application provide an electrolyte comprising a fluorinated organosilane compound and a sulfur-containing organic compound.

[0029] It should be noted that the fluorinated organosilane compounds and sulfur-containing organic compounds in the electrolyte jointly participate in the reconstruction of the electrode interface film, synergistically constructing a composite interface film with both high ionic conductivity and excellent structural stability. On the one hand, relying on the dense protective advantage of the sulfur-containing organic compounds, it effectively isolates the electrolyte from poor contact with the electrode, suppresses high-temperature side reactions, and stabilizes the electrode structure; on the other hand, by leveraging the high conductive film-forming advantage of the fluorinated organosilane compounds, it optimizes the interface microstructure, reduces interfacial contact impedance and charge transfer impedance, and lowers the overall internal resistance of the cell.

[0030] It should be noted that simply adding sulfur-containing organic compounds alone can lead to problems such as high interfacial impedance and severe polarization. Therefore, it is necessary to add fluorinated organosilicon compounds at the same time to solve the problem of high temperature that accompanies the reduction of cell impedance, which in turn leads to the degradation of the battery's electrochemical performance.

[0031] In this embodiment, sulfur-containing organic compounds in the electrolyte preferentially undergo oxidation at the positive electrode interface compared to the solvent, selectively constructing a dense protective layer in situ on the positive electrode surface. This dense protective layer effectively blocks direct contact between solvent molecules and the positive electrode active material, suppressing harmful side reactions such as continuous electrolyte decomposition and electrode interface corrosion under high-temperature, high-rate fast charging conditions. It reduces by-product accumulation and structural damage to the positive electrode active material, fundamentally alleviating the problem of rapid battery performance degradation under high-temperature environments and improving the cell's high-temperature storage and high-temperature cycling stability. Simultaneously, fluorinated organosilane compounds in the electrolyte possess excellent film-forming properties, inducing the formation of a thin, highly efficient positive electrode electrolyte interphase (CEI) film at the positive and negative electrode interfaces. This reduces charge transfer impedance and ion transport resistance across the interface, providing a foundation for rapid ion conduction during high-rate fast charging.

[0032] In summary, the electrolyte forms a synergistic system with the other two components, which effectively reduces the overall impedance of the battery cell, meets the requirements of high-rate fast charging, improves the interface stability and cycle life of the battery under high-temperature conditions, and balances the battery's fast charging performance and high-temperature service performance.

[0033] Optionally, in one embodiment, the fluorinated organosilanes have the chemical formula I.

[0034] R1, R2, and R3 independently include substituted or unsubstituted groups having 1 to 5 carbon atoms, and the groups include at least one of alkyl, aryl, alkenyl, alkynyl, and alkoxy groups.

[0035] It should be noted that R1 can be a substituted or unsubstituted group with 1 to 5 carbon atoms, R2 can be a substituted or unsubstituted group with 1 to 5 carbon atoms, and R3 can be a substituted or unsubstituted group with 1 to 5 carbon atoms. The number of carbon atoms can be one of 1, 2, 3, 4, or 5.

[0036] For example, the unsubstituted alkyl group can be at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, and isopentyl.

[0037] The substituents can be fluorinated; for example, the substituted alkyl group can be at least one of fluoromethyl and fluoroethyl.

[0038] The substituents can be methoxy or ethoxy substituted; for example, the substituted alkyl group can be at least one of methoxymethyl or ethoxyethyl.

[0039] Alkoxy groups can be methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, pentylooxy, etc. Alkenyl groups can be vinyl, allyl, 1-butenyl, isobutenyl, pentenyl, etc. Alkynyl groups can be ethynyl, propynyl, butynyl, pentynyl, etc. Aryl groups can be phenyl, etc.

[0040] In this embodiment, silicon-based functional groups and fluorine atoms are introduced into the molecular structure of the fluorine-containing organosilicon compound, which can generate a thin silicon-fluorine composite CEI passivation film with excellent ionic conductivity in situ; optimize the microstructure of the positive electrode interface, reduce charge transfer impedance and interface polarization, and work together with the interface protection effect of sulfur-containing organic compounds to stabilize the electrode interface, thereby reducing the overall impedance of the cell, improving fast charging capability, and improving the battery's high-temperature cycle degradation defects.

[0041] Optionally, in one embodiment, the fluorinated organosilane compound includes at least one of the following chemical formulas:

[0042] It should be noted that R1, R2, and R3 in Formulas II, III, and IV are all unsubstituted alkyl groups, and the number of carbon atoms in the alkyl groups of R1, R2, and R3 is less than or equal to 2. For example, the number of carbon atoms can be either 1 or 2.

[0043] Specifically, in chemical formula II, R1, R2, and R3 are all unsubstituted alkyl groups, wherein the alkyl group is methyl and has 1 carbon atom.

[0044] In chemical formula III, R1, R2, and R3 are all unsubstituted alkyl groups, of which R1 and R2 are unsubstituted methyl groups with 1 carbon atom; and R3 is an unsubstituted ethyl group with 2 carbon atoms.

[0045] In chemical formula IV, R1, R2, and R3 are all unsubstituted alkyl groups, wherein the alkyl group is an ethyl group with 2 carbon atoms.

[0046] In the embodiments of this application, the fluorinated organosilicon compounds with the above-mentioned structures are all saturated short-chain alkyl groups. Saturated short-chain alkyl groups have weak polarity and excellent compatibility with solvents in the electrolyte, enabling uniform dispersion. Alkyl groups have high chemical stability, are not easily decomposed ineffectively at room temperature, and have high utilization rate. At the same time, the steric hindrance of saturated short-chain alkyl groups is moderate, which can control the positive electrode CEI film to be a thin and dense microstructure, avoiding the increase in impedance caused by the thickness of the interface film. The hydrophobic properties of alkyl groups can effectively isolate the positive electrode interface from the corrosion of solvents in the electrolyte, and the excellent temperature oxidation resistance of saturated carbon chains can improve the high-temperature cycle stability of the battery. Combined with the controllable decomposition of the central silicon-fluorine active sites, a positive electrode interface film with high ionic conductivity, flexible structure, and strong stability is synergistically constructed. While reducing the positive electrode interface impedance and adapting to fast charging conditions, it effectively suppresses interface side reactions at high temperatures, achieving synergistic optimization of fast charging performance and high-temperature performance.

[0047] Optionally, in one embodiment, the sulfur-containing organic compound includes at least one of 1,3-propanesulfonate lactone (PS), propenyl-1,3-sulfonate lactone (PST), vinyl sulfate (DTD), vinyl sulfite (ES), and methylene disulfonate (MMDS).

[0048] It should be noted that the above-mentioned sulfur-containing organic compounds are all cyclic sulfur-containing polar compounds, containing sulfonate / sulfate / sulfite cyclic functional groups, with moderate oxidation potential and controllable electrochemical activity, and can preferentially undergo oxidation reactions at high positive electrode potentials compared to the solvent in the electrolyte.

[0049] In this embodiment, the oxidation decomposition potential of the aforementioned sulfur-containing organic compounds is lower than that of non-aqueous solvents in conventional electrolytes such as ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC). Under fast-charging high-voltage and high-temperature conditions, they can preferentially oxidize and polymerize at the positive electrode interface, preemptively occupying the positive electrode active sites; this avoids the continuous oxidation and decomposition of the solvent directly on the positive electrode surface, reducing solvent side reactions from the source. After decomposition, the aforementioned sulfur-containing organic compounds generate thioinorganic complexes, sulfonates, and sulfate products, constructing a dense, chemically inert, and high-temperature oxidation-resistant solid protective layer on the positive electrode surface: the film layer is dense and non-porous, physically isolating solvents and free water molecules from contact with the positive electrode active material; it is resistant to high-temperature and high-voltage corrosion, inhibits continuous interfacial side reactions at high temperatures, and solves the problem of high-temperature performance degradation in fast-charging systems. In addition, the aforementioned sulfur-containing organic compounds have good solubility with solvents and lithium salts in the electrolyte, do not separate, precipitate, or corrode the electrode sheet; and are suitable for mass-production electrolyte formulation systems.

[0050] Optionally, in one embodiment, the mass percentage of sulfur-containing organic compounds is a%, based on the mass of the electrolyte, wherein the value of a ranges from 0.1 to a ≤ 3.5.

[0051] For example, the value of 'a' can be a range of one or both of the following: 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%.

[0052] When the sulfur-containing organic compound is 1,3-propanesulfonate lactone, its mass percentage content can be one of 0.5%, 0.8%, 1.0%, 1.5%, 2.0%, or any two of these values.

[0053] When the sulfur-containing organic compounds are 1,3-propanesulfonate lactone and vinyl sulfate, their mass percentage content can be one of 1.0%, 1.5%, 2.0%, 2.5%, or any two of them; wherein, when the mass percentage content of the sulfur-containing organic compounds is 1.0%, 1.5%, 2.0%, 2.5%, the corresponding mass percentage content of 1,3-propanesulfonate lactone and vinyl sulfate in the sulfur-containing organic compounds are (0.5%, 0.5%), (0.9%, 0.6%), (1.0%, 1.0%), and (1.5%, 1.0%), respectively.

[0054] When the sulfur-containing organic compound is methylene disulfonate, its mass percentage content can be one of 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, or any two of these values.

[0055] In the embodiments of this application, the mass percentage of sulfur-containing organic compounds is within the above-mentioned range. This allows the sulfur-containing organic compounds to form a dense, stable, and appropriately thick protective film on the surface of the positive electrode, thereby enhancing the battery's high-temperature resistance performance. It also prevents abnormal increases in interface impedance and, in synergy with fluorinated organosilicon compounds, effectively balances the high-rate fast charging capability and high-temperature cycle stability of the ion battery.

[0056] Optionally, in one embodiment, the mass percentage of the fluorinated organosilane compound is b%, based on the mass of the electrolyte, and the range of b is 0.01 ≤ b ≤ 1.

[0057] For example, the value of b can be a range of one or any two of the following: 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.12%, 0.15%, 0.18%, 0.20%, 0.30%, 0.40%, 0.50%, 0.80%, 1%.

[0058] When the fluorinated organosilanes are of formula II, their mass percentage content can be any one or any two of the following: 0.10%, 0.15%, 0.20%, 0.30%, 0.40%, 0.50%, and 0.80%.

[0059] When the fluorinated organosilanes are of formula III, their mass percentage content can be any one or any two of the following: 0.01%, 0.05%, 0.08%, 0.10%, 0.15%, 0.20%, 0.30%, 0.40%, and 0.50%.

[0060] When the fluorinated organosilane compound has the chemical formulas II and III, its mass percentage content can be any one or any two of the following: 0.01%, 0.08%, 0.10%, 0.20%, 0.30%, and 0.40%. Among them, when the mass percentage content of the fluorinated organosilane compound is 0.01%, 0.08%, 0.10%, 0.20%, 0.30%, and 0.40%, the corresponding mass percentage contents of formulas II and III in the fluorinated organosilane compound are (0.005%, 0.005%), (0.05%, 0.03%), (0.06%, 0.04%), (0.10%, 0.10%), (0.18%, 0.12%), and (0.20%, 0.20%), respectively.

[0061] In this embodiment, the mass percentage of fluorinated organosilanes is within the above-mentioned range, ensuring that there is a sufficient amount of silicon and fluorine components in the electrolyte. These components can preferentially participate in the electrochemical reaction at the positive electrode interface, inducing the formation of a uniform, thin, and highly ionicly conductive silicon-fluorine composite interface film. This avoids excessive deposition and cross-linking of the interface film, effectively mitigating the impedance increase problem caused by a single sulfur-containing organic compound. While ensuring the stability of the battery interface at high temperatures, this reduces cell polarization and internal resistance, thereby balancing the high-rate fast charging capability and high-temperature cycle performance of the ion battery.

[0062] Optionally, in one embodiment, the mass percentage of sulfur-containing organic compounds is a%, the mass percentage of fluorine-containing organosilane compounds is b%, and the range of a / b is 0.13 to 20, based on the mass of the electrolyte.

[0063] For example, the value of a / b can be a range of one or both of the following: 0.13, 0.15, 0.18, 0.20, 0.30, 0.50, 0.80, 1.0, 3.0, 5.0, 8.0, 10, 12, 15, 17, 18, 20.

[0064] In this embodiment, a / b is limited to the above-mentioned ratio range, which can make the high-temperature interface protection effect of sulfur-containing organic compounds and the impedance reduction and high conductivity film-forming effect of fluorine-containing organosilicon compounds form a highly efficient synergy. While effectively blocking the solvent side reaction of the electrolyte and improving the high-temperature performance of the battery, it reduces the overall interface impedance of the cell, and takes into account the high-rate fast charging capability and wide-temperature-range cycle stability of the ion battery, so that the comprehensive performance reaches the optimal level.

[0065] Optionally, in one embodiment, the electrolyte further includes oxalate phosphate, which includes at least one of lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate.

[0066] It should be noted that lithium difluorodioxalate phosphate (LiDFOP) has a structure consisting of two F atoms and two oxalate atoms, resulting in balanced film formation, optimal overall performance, moderate film formation at both positive and negative electrodes, small impedance increase, strong ability to suppress side reactions at high temperatures, and the strongest versatility. It is suitable for electrochemical devices that can handle fast charging, high-temperature cycling, and room-temperature cycling.

[0067] Lithium tetrafluorooxalate phosphate (LiTFOP) has a structure consisting of 4 F atoms and 1 oxalate atom. It has the advantages of the highest fluorine content, rich inorganic LiF phase, extremely high interfacial ionic conductivity, and outstanding impedance reduction and fast charging performance. However, due to the low oxalate atom content, its ability to chelate metal ions is slightly weaker. It is suitable for electrochemical devices that focus on high-rate fast charging and low internal resistance requirements.

[0068] In the embodiments of this application, the above-mentioned oxalate phosphate has a chelating structure of fluorine group, phosphate group and oxalate, which can participate in the construction of positive and negative electrode interface films at the same time, and optimize the compactness and ion conduction performance of negative electrode electrolyte interface film (SEI film) and positive electrode electrolyte interface film (CEI film); oxalate group can effectively chelate transition metal ions, inhibit positive electrode metal dissolution and interfacial side reactions, and fluorinated phosphate structure can improve the high voltage resistance and thermal stability of electrolyte and reduce cell interface impedance.

[0069] Optionally, in one embodiment, the mass percentage content of oxalate phosphate ranges from 0.1% to 1% based on the mass of the electrolyte.

[0070] For example, the mass percentage of oxalate phosphate can be a range of one or both of the following: 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%.

[0071] When the oxalate phosphate is lithium difluorodioxalate phosphate, its mass percentage content can be one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, or any two of these values.

[0072] When the oxalate phosphate is lithium tetrafluorooxalate phosphate, its mass percentage content can be one or any two of the following: 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, and 0.8%.

[0073] When the oxalate phosphate is lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate, its mass percentage content can be one or any two of the following: 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, and 0.7%. Among them, when the mass percentage content of oxalate phosphate is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, and 0.7%, the corresponding mass percentage contents of lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate in the oxalate phosphate are (0.1%, 0.1%), (0.18%, 0.12%), (0.22%, 0.18%), (0.25%, 0.25%), (0.4%, 0.2%), and (0.4%, 0.3%).

[0074] In this embodiment, the mass percentage of oxalate phosphate is within the above range, which allows oxalate phosphate to participate appropriately in the construction of the SEI / CEI composite interface film. It works synergistically with sulfur-containing organic compounds and fluorine-containing organosilicon compounds to enhance the stability of the electrode interface, suppress the dissolution of transition metals and high-temperature side reactions without sacrificing fast-charging performance, and further balance the low-impedance fast-charging characteristics and high-temperature long-cycle service performance of the ion battery.

[0075] Optionally, in one embodiment, the electrolyte further includes a first film-forming additive, which includes at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), difluoroethylene carbonate, fluoropropylene carbonate, and methyl vinylene carbonate.

[0076] It should be noted that fluoroethylene carbonate (FEC) has a fluorine-containing structure, and the film formed is rich in LiF. The SEI film has high mechanical strength, high pressure and high temperature resistance, and a strong effect in suppressing negative electrode side reactions. It is suitable for high-temperature stable and high-voltage systems, and improves high-temperature cycling and interfacial corrosion resistance.

[0077] Vinylene carbonate (VC) has a highly active carbon-carbon double bond structure, which is easy to polymerize and crosslink to form a flexible and dense organic phase SEI film. The film has excellent flexibility and is suitable for the volume expansion of silicon-based anodes. It can improve cycle life and inhibit the breakage of anode structure.

[0078] In the embodiments of this application, the aforementioned first film-forming additives are all unsaturated / fluorinated cyclic carbonates containing double bond structures or fluorine-substituted structures. They have suitable redox potentials and can preferentially decompose compared to EC, DMC, and EMC basic solvents. They simultaneously optimize the negative electrode SEI film and assist in improving the positive electrode CEI interface. They form a multi-component synergistic system with sulfur-containing organic compounds and fluorinated organosilicon compounds, further reducing the cell interface impedance, suppressing high-temperature gas generation and capacity decay. While ensuring the high-rate fast charging performance of the battery, they also improve the high-temperature cycle life and safety of use.

[0079] Optionally, in one embodiment, the mass percentage of the first film-forming additive ranges from 0.2% to 8% based on the mass of the electrolyte.

[0080] For example, the mass percentage of the first film-forming additive can be a range of one or any two of 0.2%, 0.5%, 0.8%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, and 8.0%.

[0081] When the first film-forming additive is fluoroethylene carbonate, its mass percentage content can be one or any two of the following: 0.2%, 0.3%, 0.4%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, and 5.0%.

[0082] When the first film-forming additive is vinylene carbonate, its mass percentage content can be one or any two of the following: 0.2%, 0.25%, 0.3%, 0.5%, 0.8%, 1.0%, 2.0%.

[0083] When the first film-forming additive is fluoroethylene carbonate and vinylene carbonate, its mass percentage content can be one or any two of the following: 0.2%, 0.3%, 0.5%, 0.8%, 1.0%, and 1.5%. When the mass percentage content of the first film-forming additive is 0.2%, 0.3%, 0.5%, 0.8%, 1.0%, and 1.5%, the corresponding mass percentage contents of fluoroethylene carbonate and vinylene carbonate in the first film-forming additive are (0.1%, 0.1%), (0.16%, 0.14%), (0.25%, 0.25%), (0.5%, 0.3%), (0.6%, 0.4%), and (0.8%, 0.7%), respectively.

[0084] In this embodiment, the mass percentage of the first film-forming additive is within the above-mentioned range, which can moderately regulate the microstructure and thickness of the electrode interface film, construct a dense, flexible, low-resistance stable interface layer, and form a synergistic combination with sulfur-containing organic compounds and fluorine-containing organosilicon compounds. While effectively reducing cell impedance and improving fast charging capability, it also suppresses interface degradation under high-temperature conditions, so that the rate performance, high-temperature stability and long cycle life of the ion battery can reach the optimal level.

[0085] Optionally, in one embodiment, the electrolyte further includes a non-aqueous solvent; The non-aqueous solvent includes at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate.

[0086] It should be noted that ethylene carbonate (EC) has high dielectric properties, strong film-forming ability, and high temperature resistance, making it a basic film-forming framework for electrolytes.

[0087] Dimethyl carbonate (DMC) has the lowest viscosity, fast ion conduction, and significant fast-charging gain.

[0088] Ethyl methyl carbonate (EMC) has an asymmetric structure, better thermal stability than DMC, is not easily decomposed at high temperatures, and balances high and low temperature performance.

[0089] In the embodiments of this application, the above-mentioned non-aqueous solvents are all cyclic / chain carbonate non-aqueous solvents, which are the main matrix of the electrolyte. They have excellent compatibility with various functional additives (such as sulfur-containing organic compounds, fluorine-containing organosilicon compounds, oxalate phosphate, first film-forming additives, etc.), and are used to completely dissolve lithium salts and various functional additives to form a uniform and stable liquid phase system, providing a continuous medium for ion migration and conduction.

[0090] Optionally, in one embodiment, the electrolyte further includes a lithium salt; wherein the lithium salt includes at least one of lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethanesulfonyl)methyl, lithium hexafluoroantimonylate, lithium hexafluoroarsenate, and lithium hexafluorophosphate.

[0091] It should be noted that lithium difluorophosphate (LiPO2F2) preferentially forms films on both the positive and negative electrodes. The dense and low-resistivity interfacial film reduces the interface impedance of the positive electrode, inhibits high-voltage and high-temperature solvent oxidation, and improves high-temperature cycling and gas expansion.

[0092] Lithium bisfluorosulfonyl imide (LiFSI) has high conductivity, low viscosity, and strong dissociation ability, which improves the performance of fast charging at high rates; it is resistant to hydrolysis and has excellent thermal stability, which reduces electrolyte decomposition; it is suitable for high rate systems.

[0093] Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) has a fluorine-containing sulfonyl structure, exhibits extremely high voltage and heat resistance, good interface stability, and corrosion resistance in high-voltage positive electrodes, making it suitable for high-voltage and high-temperature operating conditions.

[0094] Lithium tetrafluoroborate (LiBF4) has a boron-fluorine structure, outstanding low-temperature performance, and is suitable for wide-temperature systems.

[0095] Lithium bis(oxalateborate)borate (LiBOB) has oxalate chelation and a rigid boric acid framework, resulting in extremely tough film formation, high temperature resistance, and anti-dissolution properties, effectively improving high-temperature cycle life.

[0096] Lithium hexafluorophosphate (LiPF6) is the core lithium salt standard for commercial power batteries and energy storage batteries.

[0097] In this embodiment, the lithium salt has a stable anionic structure and high dissociation efficiency, which can reduce electrolyte viscosity and increase lithium ion migration rate. It is highly compatible with sulfur-containing ester compounds, fluorinated organosilicon compounds, oxalate phosphate, and the first film-forming additive in the electrolyte, effectively improving the electrolyte ionic conductivity, reducing ion transport resistance and cell polarization, and enhancing the battery's high-rate fast charging capability. At the same time, it can synergistically participate in the construction of the positive and negative electrode SEI and CEI composite interface films to generate a stable passivation layer rich in fluorides, borates, and phosphates.

[0098] Secondly, this application proposes a method for preparing an electrolyte, applicable to the aforementioned electrolyte, the method comprising: A second film-forming additive is obtained by mixing a fluorinated organosilane compound and a sulfur-containing organic compound. The electrolyte is obtained by using a second film-forming additive.

[0099] It should be noted that the electrolyte preparation process must be carried out under an inert gas atmosphere. This inert gas atmosphere can be nitrogen, argon, or similar gases.

[0100] It should be noted that obtaining an electrolyte based on the second film-forming additive includes obtaining an electrolyte based on the second film-forming additive and other necessary solvents for preparing the electrolyte, such as non-aqueous solvents and lithium salts.

[0101] In this embodiment, the preparation method described above utilizes the oxidation reaction of sulfur-containing organic compounds at the positive electrode interface, prioritizing the solvent in the electrolyte, to construct a dense protective layer in situ on the positive electrode surface. This dense protective layer fundamentally alleviates the problem of rapid battery performance degradation under high-temperature conditions, improving the cell's high-temperature storage and high-temperature cycling stability. Simultaneously, the introduction of fluorinated organosilane compounds possesses excellent film-forming properties, inducing the formation of a thin, highly efficient positive electrode-electrolyte interface film at the positive and negative electrode interfaces. This reduces charge transfer impedance and ion transport resistance across the interface, providing a foundation for rapid ion conduction during high-rate fast charging. Furthermore, the above preparation method is suitable for the large-scale production of electrolytes, while simultaneously considering performance and safety.

[0102] Thirdly, this application proposes an electrochemical device comprising a positive electrode, a negative electrode, a diaphragm, and the aforementioned electrolyte, wherein the diaphragm is disposed between the positive electrode and the negative electrode.

[0103] For example, an electrochemical device can be a battery.

[0104] Optionally, in one embodiment, the positive electrode includes a positive current collector and a positive active material disposed on the surface of the positive current collector.

[0105] For example, the positive electrode active material includes at least one of lithium cobalt oxide, nickel-cobalt-manganese ternary oxide, nickel-cobalt-aluminum ternary oxide, lithium iron phosphate, lithium manganese iron phosphate, and lithium manganate.

[0106] Optionally, in one embodiment, the positive electrode further includes a conductive agent and a binder. The conductive agent includes at least one of conductive graphite, conductive carbon black, carbon nanotubes, and graphene. The binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).

[0107] It should be noted that conductive graphite / conductive carbon black is a basic conductive phase, which features low cost and easy dispersion, can fill the tiny gaps between the positive electrode active material particles, construct a basic conductive network, and ensure the basic conductive performance of the electrode sheet.

[0108] Carbon nanotubes / graphene are high-efficiency conductive phases, which have ultra-high electronic conductivity and aspect ratio (for carbon nanotubes) / specific surface area (for graphene), can bridge between large particles of the positive electrode active material, construct a three-dimensional continuous high-efficiency conductive network, reduce the contact internal resistance of the electrode sheet, and improve the rate performance of the battery.

[0109] Polyvinylidene fluoride (PVDF, also known as polyvinylidene difluoride) is the mainstream binder for battery positive electrodes, which has excellent compatibility with positive electrode active materials and conductive agents, strong adhesion, resistance to electrolyte corrosion, and good electrochemical stability.

[0110] Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is obtained by introducing hexafluoropropylene on the basis of PVDF, which improves the flexibility and electrolyte absorption of the binder, makes the electrode sheet easier to be wetted by the electrolyte, shortens the ion diffusion path, relieves the volume stress of the electrode sheet during cycling, further improves the cycle life, and can be applied to high-end high-cycle batteries.

[0111] Optionally, in one embodiment, the negative electrode includes a negative electrode current collector and a negative electrode active material disposed on the surface of the negative electrode current collector.

[0112] Optionally, in one embodiment, the negative electrode active material includes a carbon-based material, the carbon-based material includes one of graphite, amorphous carbon, and carbon nanomaterials, the graphite includes at least one of natural graphite and artificial graphite; the carbon nanomaterial includes at least one of graphene, graphene oxide, carbon nanotubes, and carbon fibers.

[0113] Optionally, in one embodiment, the negative electrode active material includes graphite and silicon, and the silicon includes at least one of silicon-carbon particles, pure silicon particles, and SiO x (0<x<2) particles.

[0114] Optionally, in one embodiment, the negative electrode active material may further include one of tin-based materials and titanium-based materials. Tin-based materials include at least one of elemental tin, Sn / C, and SnO2 / C; titanium-based materials include at least one of lithium titanate (LTO), lithium titanate / graphite composite, and lithium titanate / carbon nanotube composite.

[0115] Optionally, in one embodiment, the negative electrode further includes a conductive agent and a binder; the conductive agent includes at least one of conductive graphite, conductive carbon (SP), carbon black, carbon nanotubes, and graphene; the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, sodium alginate, and polyvinylidene fluoride.

[0116] Fourthly, embodiments of this application provide an electrochemical energy storage device, which includes the electrochemical device described above.

[0117] For example, an electrochemical energy storage device can be a battery pack.

[0118] Fifthly, embodiments of this application provide an electrical device including the aforementioned electrochemical energy storage device, wherein the electrochemical energy storage device serves as the power supply for the electrical device.

[0119] For example, electrical devices can be vehicles, smart home appliances, robots, power tools, smart wearable devices, mobile electronic devices (such as mobile phones, computers, tablets), drones, and so on.

[0120] The above-described embodiments of the electrochemical energy storage device and the power consumption device include the aforementioned electrochemical device and can achieve the same technical effect. To avoid repetition, they will not be described again here. For relevant details, please refer to the description of the electrochemical device embodiments.

[0121] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.

[0122] The present application will be described in detail below through embodiments.

[0123] Test method: (1) DC internal resistance (DCR) test: After the battery is charged at a constant current of 0.33C to 4.35V, it switches to constant voltage charging until the current limit drops to 0.05C, at which point it is fully charged.

[0124] The fully charged battery was stored at 60℃ for 7 days. After the high-temperature storage, it was first fully discharged at a constant current of 0.33C, then charged again at a constant current of 0.33C until the voltage reached 4.35V. Subsequently, it was charged at a constant voltage of 4.35V until the current dropped to 0.05C. After being left to stand at room temperature (25℃) for 5 minutes, it was discharged at a constant current of 0.33C for 1.5 hours. The battery was then placed in a low-temperature environment of -20℃ for 4 hours. After the temperature stabilized, the current battery voltage was collected and recorded as U1. Immediately afterward, it was discharged at a high current of 4C for 10 seconds, and the terminal voltage at the end of the discharge was collected and recorded as U2. The 4C discharge current was recorded as I. After the test, the battery was left to stand for 0.5 hours to recover. The voltage and current sampling time interval was 0.1s throughout the test. The formula for calculating the DC internal resistance is: DCR=(U1-U2) / I Wherein, U1 is the initial steady-state voltage after being placed at low temperature and before being discharged with high current; U2 is the instantaneous voltage after a short discharge of 4C high current for 10s; U1-U2 is the voltage drop value caused by the instantaneous loading of high current; I is the constant operating current of 4C discharge; the voltage unit is volt (V) and the current unit is ampere (A).

[0125] (2) High-temperature storage capacity test: Place the battery in a 25°C constant temperature chamber for 30 minutes to allow the battery temperature to stabilize. Charge the battery at a constant current of 0.33C to 4.35V, then switch to constant voltage charging at 4.35V until the cutoff current is 0.05C. After resting for 10 minutes, discharge the battery at a constant current of 0.33C to the cutoff voltage of 3V, and record the discharge capacity as the initial capacity C0. After resting for another 10 minutes, charge the battery at a constant current of 0.33C to 4.35V, then charge it at a constant voltage until the current drops to 0.05C, completing the full charge. Store the fully charged battery in a sealed environment at 60℃ for 60 days. After the high-temperature storage period, remove the battery and discharge it at a constant current of 0.33C to 3V. After resting for 10 minutes, charge the battery at a constant current of 0.33C to 4.35V, then charge it at a constant voltage to 0.05C, rest for 10 minutes, and then discharge it at a constant current of 0.33C to 3V again, recording the discharge capacity as the storage capacity C1. The formula for calculating the capacity retention rate is: Capacity retention rate = C1 / C0 * 100% Wherein, C0 is the initial rated discharge capacity of the battery under standard operating conditions without high-temperature storage, serving as a benchmark reference; C1 is the remaining actual discharge capacity after being stored at 60℃ for 60 days, tested under the same conditions.

[0126] Example 1 (1) Preparation of positive electrode sheet The positive electrode active material (LiNi) 0.6 Co 0.1 Mn 0.3(NCM613), conductive agent (conductive carbon and carbon nanotubes), binder (polyvinylidene fluoride) in a ratio of 96:1:0.5:2.5 (LiNi) 0.6 Co 0.1 Mn 0.3 A positive electrode slurry is prepared by mixing conductive carbon, carbon nanotubes, and polyvinylidene fluoride (PVDF) in N-methylpyrrolidone at a mass ratio of 1:1 and stirring until homogeneous. Aluminum foil is used as the positive electrode current collector, and the slurry is coated onto its surface. The foil is dried at 120°C for 1 hour, followed by cold pressing, cutting, and slitting to obtain the positive electrode sheet.

[0127] (2) Preparation of negative electrode sheet The negative electrode active material (artificial graphite), conductive agent (conductive carbon), and binder (sodium carboxymethyl cellulose and styrene-butadiene rubber) were mixed in deionized water at a mass ratio of 96.35:1.2:1.05:1.3 (artificial graphite:conductive carbon:sodium carboxymethyl cellulose:styrene-butadiene rubber) and stirred evenly to obtain a negative electrode slurry. Copper foil was used as the negative electrode current collector, and the negative electrode slurry was coated onto the surface of the current collector. The coating was dried at 120°C for 1 hour, followed by cold pressing, cutting, and slitting to obtain the negative electrode sheet.

[0128] (3) Preparation of electrolyte Under an argon atmosphere at 10°C, a non-aqueous solvent was added and mixed with ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) in a volume ratio of 30:40:30. Subsequently, 0.5% of the first film-forming additive (fluoroethylene carbonate), 0.5% of the sulfur-containing organic compound (1,3-propanesulfonate lactone), 0.5% of the fluorinated organosilane compound (Formula II), and 12.5% ​​of the lithium salt (lithium hexafluorophosphate LiPF6) were added to obtain the electrolyte.

[0129] (4) Battery preparation A 7-micron thick porous polyethylene film was selected as the membrane substrate. Boehmite ceramic slurry was coated on one side of the polyethylene substrate and dried and cured to form a 2-micron thick boehmite ceramic coating. A PVDF adhesive coating was coated on both sides of the ceramic coating. After drying, rolling and shaping, a composite membrane was obtained.

[0130] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to act as a separator. The side coated with boehmite ceramic is aligned with the positive electrode. The electrodes are then stacked, placed in an aluminum-plastic film, dried at 80°C, and then injected with the electrolyte. After vacuum sealing, settling, formation, and shaping, the battery is obtained.

[0131] Example 2 The difference between Example 2 and Example 1 is as follows: In Example 2, the sulfur-containing organic compound in the preparation of the electrolyte in step (3) was adjusted to 1% ethylene sulfate.

[0132] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0133] Example 3 The difference between Example 3 and Example 1 is as follows: In Example 3, the sulfur-containing organic compound in the preparation of the electrolyte in step (3) was changed to methylene methane disulfonate.

[0134] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0135] Example 4 The difference between Example 4 and Example 1 is as follows: In Example 4, the sulfur-containing organic compound in the preparation of the electrolyte in step (3) was adjusted to 0.2% propenyl-1,3-sulfonyl lactone; the fluorinated organosilicon compound was adjusted to Formula III.

[0136] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0137] Example 5 The difference between Example 5 and Example 1 is as follows: In Example 5, the sulfur-containing organic compounds in the preparation of the electrolyte in step (3) were adjusted to 0.5% 1,3-propanesulfonate lactone and 1% vinyl sulfate.

[0138] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0139] Example 6 The difference between Example 6 and Example 1 is: In Example 6, in the preparation of the electrolyte in step (3), the sulfur-containing organic compound was adjusted to 0.5% 1,3-propanesulfonate lactone and 1% vinyl sulfate, and the first film-forming additive was adjusted to 0.3% vinylene carbonate.

[0140] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0141] Example 7 The difference between Example 7 and Example 1 is as follows: In Example 7, the sulfur-containing organic compounds in the preparation of the electrolyte in step (3) were adjusted to 0.8% 1,3-propanesulfonate lactone, 1.5% vinyl sulfate and 0.5% methanedisulfonate methylene ester.

[0142] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0143] Example 8 The difference between Example 8 and Example 1 is: In Example 8, the sulfur-containing organic compound in the preparation of the electrolyte in step (3) was adjusted to 2% ethylene sulfate and the fluorine-containing organosilicon compound was adjusted to 0.1%.

[0144] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0145] Example 9 The difference between Example 9 and Example 1 is as follows: In Example 9, in the preparation of the electrolyte in step (3), the sulfur-containing organic compound was adjusted to 0.1% propenyl-1,3-sulfonyl lactone and the fluorinated organosilicon compound was adjusted to 0.8%.

[0146] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0147] Example 10 The difference between Example 10 and Example 1 is as follows: In Example 10, the sulfur-containing organic compounds in the preparation of the electrolyte in step (3) were adjusted to 0.5% 1,3-propanesulfonate lactone and 1% vinyl sulfate, and 0.3% oxalate phosphate (lithium difluorodioxalate phosphate) was added.

[0148] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0149] Example 11 The difference between Example 11 and Example 1 is as follows: In Example 11, the sulfur-containing organic compounds in the preparation of the electrolyte in step (3) were adjusted to 0.5% 1,3-propanesulfonate lactone and 1% vinyl sulfate, and 0.3% oxalate phosphate (lithium tetrafluorooxalate phosphate) was added.

[0150] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0151] Example 12 The difference between Example 12 and Example 1 is as follows: In Example 12, in the preparation of the electrolyte in step (3), the sulfur-containing organic compounds were adjusted to 0.5% 1,3-propanesulfonate lactone and 1% vinyl sulfate, and 0.5% oxalate phosphate (lithium tetrafluorooxalate phosphate) was added.

[0152] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0153] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: In Comparative Example 1, no sulfur-containing organic compounds or fluorine-containing organosilicon compounds were added during the preparation of the electrolyte in step (3).

[0154] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0155] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is as follows: In Comparative Example 2, no first film-forming additive and fluorinated organosilane compound were added during the preparation of the electrolyte in step (3).

[0156] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0157] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is as follows: In Comparative Example 3, no first film-forming additive and sulfur-containing organic compound were added during the preparation of the electrolyte in step (3).

[0158] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0159] The batteries obtained in each embodiment and comparative example were subjected to DC internal resistance testing and high-temperature storage capacity testing. The results are shown in Table 1.

[0160] Table 1

[0161] According to the results in Table 1, compared with the comparative examples, the DCR values ​​of the batteries in the examples are all less than or equal to 26, while the DCR values ​​of the comparative examples are all greater than 27. It can be seen that the addition of sulfur-containing organic compounds and fluorine-containing organosilicon compounds to the electrolyte in the embodiments of this application can reduce the DCR of the battery cell and improve the capacity retention rate. This is because sulfur-containing organic compounds preferentially oxidize at the positive electrode interface, forming a dense protective layer on the surface of the positive electrode, which isolates the electrolyte solvent from the positive electrode from side reactions. However, the interface impedance is high. On the other hand, fluorine-containing organosilicon compounds can form a thin and highly conductive ion-conducting CEI film. The two can work together to form a highly conductive lithium-ion and interface-stable SEI film, thus taking into account both fast charging and high-temperature performance.

[0162] Comparing Examples 1-9, the a / b ratio of 1.3-20 indicates better performance. When the ratio is too low, the sulfur-containing organic compound is at a disadvantage in competition because the amount of sulfur-containing organic compound added is less than that of fluorinated organosilane compound, and fluorinated organosilane compound becomes the main additive, resulting in an insufficiently dense interfacial film. When the ratio is high, sulfur-containing organic compound dominates, forming a high-resistivity interfacial film, leading to a deterioration in overall performance.

[0163] In Examples 10-12, the addition of oxalate phosphate to the electrolyte can further reduce the cell DCR and improve the capacity retention rate.

[0164] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0165] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.

Claims

1. An electrolyte, characterized in that, The electrolyte includes fluorinated organosilanes and sulfur-containing organic compounds.

2. The electrolyte according to claim 1, characterized in that, The chemical formula of the fluorinated organosilanes is Formula I. R1, R2, and R3 independently include substituted or unsubstituted groups having 1 to 5 carbon atoms, and the groups include at least one of alkyl, aryl, alkenyl, alkynyl, and alkoxy groups.

3. The electrolyte according to claim 2, characterized in that, The fluorinated organosilane compound includes at least one of the following chemical formulas. 。 4. The electrolyte according to any one of claims 1-3, characterized in that, The sulfur-containing organic compound includes at least one of 1,3-propanesulfonate lactone, propenyl-1,3-sulfonate lactone, vinyl sulfate, vinyl sulfite, and methylene disulfonate.

5. The electrolyte according to any one of claims 1-3, characterized in that, Based on the mass of the electrolyte, the mass percentage of the sulfur-containing organic compound is a%, and the mass percentage of the fluorinated organosilane compound is b%. Wherein, the range of 'a' is 0.1 ≤ a ≤ 3.5; and / or, The range of b is 0.01≤b≤1.

6. The electrolyte according to claim 5, characterized in that, The range of a / b is 0.13 to 20.

7. The electrolyte according to any one of claims 1-6, characterized in that, The electrolyte also includes oxalate phosphate, which includes at least one of lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate.

8. The electrolyte according to claim 7, characterized in that, The mass percentage of oxalate phosphate is in the range of 0.1% to 1% based on the mass of the electrolyte.

9. The electrolyte according to any one of claims 1-6, characterized in that, The electrolyte further includes a first film-forming additive, which includes at least one of fluoroethylene carbonate, vinylene carbonate, difluoroethylene carbonate, fluoropropylene carbonate, and methyl vinylene carbonate.

10. The electrolyte according to claim 9, characterized in that, The mass percentage of the first film-forming additive ranges from 0.2% to 8% based on the mass of the electrolyte.

11. The electrolyte according to any one of claims 1-10, characterized in that, The electrolyte also includes a non-aqueous solvent and / or lithium salt; The non-aqueous solvent includes at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate; and / or, The lithium salt includes at least one of lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethanesulfonyl)methyl, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, and lithium hexafluorophosphate.

12. A method for preparing an electrolyte, characterized in that, The preparation method is applicable to the electrolyte according to any one of claims 1 to 11, and the preparation method includes: A second film-forming additive is obtained by mixing a fluorinated organosilane compound and a sulfur-containing organic compound. The electrolyte is obtained according to the second film-forming additive.

13. An electrochemical device, characterized in that, The electrochemical device includes a positive electrode, a negative electrode, a diaphragm, and an electrolyte according to any one of claims 1 to 11, wherein the diaphragm is disposed between the positive electrode and the negative electrode.

14. An electrochemical energy storage device, characterized in that, The electrochemical energy storage device includes the electrochemical device according to any one of claims 13.

15. An electrical appliance, characterized in that, The device includes the electrochemical energy storage device as described in claim 14, wherein the electrochemical energy storage device serves as the power supply for the electrical device.